Den Use Patterns of Endangered San Joaquin Kit Foxes in Urban Environments May Facilitate Disease Transmission - Brian L. Cypher; Alyse Gabaldon; Erica C. Kelly; Tory L. Westall; Nicole A. Deatherage (Animals)
A robust population of endangered San Joaquin kit foxes (Vulpes macrotis mutica; SJKFs) occurs in the city of Bakersfield, CA. In 2013, sarcoptic mange was detected and significantly reduced SJKF abundance. Dens may be a mode of mange mite transmission. Kit foxes use dens daily and sometimes share dens. Also, mange mites are able to live off-host in den soil for multiple days. We monitored den use patterns of 37 marked kit foxes. Radio-collared foxes were tracked to dens and then those dens were monitored with cameras for 7-day sessions, the period of time mites might persist in the dens. Other foxes used the same den as a collared fox during 89.0% of sessions and the mean number was 2.5 foxes. An average of 1.8 foxes used a den concurrently with the collared fox. During 120-day intervals, the minimum survival time for kit foxes contracting mange, collared foxes used a mean of 7.6 dens, 9.8 other foxes used the same dens, and 7.3 foxes used the dens concurrently with the collared foxes. Thus, the potential for kit foxes to transmit mange through den sharing in the urban environment is considerable and may explain the rapid spread of mange throughout this population.